Raspberry pi based Energy Monitoring System in Chemical Industry - Kavanal, Giethu; Ganesh, Rakhi; Sakkeer, Shahana; Sreelekshmi, R (International Journal of Computer Sciences and Engineering, 2025)
The main purpose of implementing Chemical industry automation is to provide required temperature, air humidity and light levels independent from outer environmental conditions. By this way maximum control from unit area will be obtained so that industry will have been handled in most efficient way. Controller type and its peripherals must satisfy required customer expectations. Traditional systems owners look forward to user friendly interface, scalable input and output ports that are compatible with any type of industrial equipment’s, faultless control system from such automation system. In addition to customer expectation, suitable software algorithm is to developed to save different mechanical conditions in single microprocessor. For related control system we should also clarify right sensors to measure present factory conditions.